DESIGN AND FABRICATION OF AN IMPROVED MOTORIZED MAIZE SHELLER/THRESHING MACHINE - ADEWALE SEDARA; EMMANUEL ODEDIRAN; SETH MANUWA (Journal of Engineering Studies and Research)
One major essential operation in processing maize is shelling of maize. Maize shelling is one of the most important processing operations carried out in maize processing since it’s among the widely consumed grains all over the world. Shelling bring out good quality of maize which not only prolong its useful life, but also increase the net profit farmers make from its mechanization. Component parts such as: frame, hopper, transmission shaft, cylinder with spikes and blower, concave with sieve, power source, pulley and bearings was designed and fabricated. It can be moved to where it’s needed this would encourage farmers to shell their maize grains on the farm.